2016
DOI: 10.1007/s00402-016-2500-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel foot–ankle orthosis in the non-operative treatment of unicompartmental knee osteoarthritis

Abstract: IntroductionUnloader braces are non-surgical treatment options for patients with unicompartmental knee osteoarthritis (OA). However, many patients do not adhere to brace treatment because of complications related to discomfort and poor fit. An alternative to knee bracing is an ankle–foot orthosis (AFO) with a lever arm that presses the lower leg into valgus or varus. The aim of this study is to evaluate the clinical benefits of this AFO for patients with unicompartmental knee OA.Materials and methodsTwenty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…So far, only a few and partly controversial results have been obtained on ankle-foot orthoses in the context of knee osteoarthritis. Studies by Petersen et al 21 and Menger et al 22 reported positive influences on pain and functional outcomes., On the contrary, the study by Sliepen et al 23 described a clinically relevant deterioration of the same measures after a six-week intervention with an ankle-foot orthosis. Our results complement this spectrum: Health-related quality of life was improved by the ankle-foot orthosis and even by the lateral wedge insole despite the only marginal biomechanical effects of the latter.…”
Section: Discussionmentioning
confidence: 97%
“…So far, only a few and partly controversial results have been obtained on ankle-foot orthoses in the context of knee osteoarthritis. Studies by Petersen et al 21 and Menger et al 22 reported positive influences on pain and functional outcomes., On the contrary, the study by Sliepen et al 23 described a clinically relevant deterioration of the same measures after a six-week intervention with an ankle-foot orthosis. Our results complement this spectrum: Health-related quality of life was improved by the ankle-foot orthosis and even by the lateral wedge insole despite the only marginal biomechanical effects of the latter.…”
Section: Discussionmentioning
confidence: 97%
“…As far as the authors are aware, there are no comparable results on AFO and limb alignment in the scientific literature. The clinical results of this investigation, however, allow the hypothesis that the positive clinical results described above with pain reduction and functional improvement may be improved by careful patient selection (16,17).…”
Section: Discussionmentioning
confidence: 86%
“…with knee osteoarthritis (14)(15)(16)(17). Nevertheless, not all patients within these cohorts benefited from AFO treatment.…”
mentioning
confidence: 99%
“…The LWIs are the most widely used to decrease the weight bearing load on the medial compartment of the knee. This type of insoles could be useful in patients with medial OA of the knee, aiming to slow down the progression of the OA process 57,58. Moreover, soft lateral wedge arch support insoles, compared with rigid ones, improve the symptoms of patients both in daily and in sports activities such as running 59…”
Section: Resultsmentioning
confidence: 99%